7. Can Recombinant Zoster Vaccine Administration Decrease the Use of Herpes Zoster-related Pain Medication Across Randomized Controlled Studies?. (31st December 2020) - Kim, Joon Hyung; Johnson, Robert; Kovac, Martina; Cunningham, Anthony L; Emmadi, Srikanth; Sullivan, Keith; Dagnew, Alemnew F; Curran, Desmond; Schuind, Anne
Abstract: Background: Older and immunocompromised adults are at increased risk for herpes zoster (HZ) and often experience persistent, severe HZ-related pain, impacting their quality of life and activities of daily living. High vaccine efficacy (VE) of the adjuvanted recombinant zoster vaccine (RZV) in preventing HZ and reducing severe and clinically significant HZ-related pain has been shown in adults ≥ 50 years of age (YOA; ZOE-50 study; NCT01165177), ≥ 70 YOA (ZOE-70; NCT01165229) and ≥ 18 YOA undergoing autologous hematopoietic stem cell transplantation (ZOE-HSCT; NCT01610414). Methods: In patients with confirmed HZ from the above phase III, randomized, placebo-controlled studies, we analyzed VE of RZV in reducing the duration of clinically significant HZ-related pain and in reducing the use and duration of HZ-related pain medication. Pain was assessed by the Zoster Brief Pain Inventory (ZBPI). Use of all HZ-related medication was recorded. Results: VE in reducing the duration of clinically significant HZ-related pain (ZBPI pain score ≥3) during HZ episodes was 38.5% (p-value: 0.0099) in RZV-vaccinated patients from the ZOE-HSCT study compared to placebo. A similar trend (not statistically significant) was observed in the ZOE-50 (VE: 26.9%; p-value: 0.4318) and ZOE-70 (VE: 28.4%; p-value: 0.1877) studies. VE in reducing the use (Table 1 ) and duration (Table 2 ) of HZ-related pain medication was 39.6% (p-value: 0.0083) and 49.3%(p-value: 0.0404), respectively, in the ZOE-70 study; corresponding positive VE estimates were also seen in the ZOE-50 and ZOE-HSCT studies. Non-opioids were used by 61.2%, 44.3% and 22.1% of patients in the ZOE-50, ZOE-70 and ZOE-HSCT studies, respectively; weak opioids by 18.6%, 13.0% and 10.8% of patients, and strong opioids by 8.0%, 2.0% and 5.3% of patients (Table 3 ). Table 1. Reduction in the use of HZ-related pain medication in patients with confirmed HZ Table 2. Reduction in the duration of HZ-related pain medication use in patients with confirmed HZ Table 3. HZ-related medication types in patients with confirmed HZ Conclusion: In addition to a high VE in preventing HZ in these studies, we also observed an attenuation of HZ-related pain, and thus lower use and duration of pain medication in breakthrough cases after RZV vaccination, thereby potentially improving patient quality of life. Funding: GlaxoSmithKline Biologicals SA Acknowledgment: Kristel Vercauteren/Sander Hulsmans (Modis c/o GSK) provided medical writing/editorial support Disclosures: Joon Hyung Kim, MD, GSK (Employee, Shareholder) Robert Johnson, MD, FRCA, GSK (Other Financial or Material Support, I accept no fees but have had expense reimbursement in the past.) Martina Kovac, MD, GSK (Other Financial or Material Support, I was an employee of GSK at the time of the study) Anthony L. Cunningham, MBBS, MD, FRACP, FRCPA, GSK (Consultant) Srikanth Emmadi, MSc, GSK (Employee) Keith Sullivan, MD, FASTCT, GSK (Consultant) Alemnew F. Dagnew, MD, GSK group of companies (Employee, Shareholder) Desmond Curran, PhD, GSK (Employee, Shareholder) Anne Schuind, MD, GSK (Employee, Other Financial or Material Support, own GSK stock options or restricted shares as part of renumeration)